2012
DOI: 10.1016/j.plantsci.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into PYR/PYL/RCAR ABA receptors and PP2Cs

Abstract: Abscisic acid (ABA) plays an essential function in plant physiology since it is required for biotic and abiotic stress responses as well as control of plant growth and development. A new family of soluble ABA receptors, named PYR/PYL/RCAR, has emerged as ABA sensors able to inhibit the activity of specific protein phosphatases type-2C (PP2Cs) in an ABAdependent manner. The structural and functional mechanism by which ABA is perceived by these receptors and consequently leads to inhibition of the PP2Cs has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 43 publications
1
90
0
Order By: Relevance
“…These data provided key structural support to understand the formation of the ternary complex between PYR/PYL-ABA-PP2C (Figure 7), which is required for fully inhibition of the PP2C activity (Miyazono et al, 2009, Dupeux et al, 2011a, Santiago et al, 2012. The example in the figure represents PYL1 inhibition of ABI1 upon ABA sensing.…”
Section: Protein Phosphatases Type 2c Pp2csmentioning
confidence: 83%
See 1 more Smart Citation
“…These data provided key structural support to understand the formation of the ternary complex between PYR/PYL-ABA-PP2C (Figure 7), which is required for fully inhibition of the PP2C activity (Miyazono et al, 2009, Dupeux et al, 2011a, Santiago et al, 2012. The example in the figure represents PYL1 inhibition of ABI1 upon ABA sensing.…”
Section: Protein Phosphatases Type 2c Pp2csmentioning
confidence: 83%
“…ABI1, ABI2, hypersensitive to ABA 1 (HAB1) and HAB2 are grouped in the same branch, whereas the second branch is formed by ABA-hypersensitive germination 1 (AHG1), AHG3/PP2CA and highly ABA inducible 1 (HAI1), HAI2 and HAI3. A second ABA-insensitive mutant, abi2-1, was also identified by Koornneef et al (1984) and the locus was cloned by Leung et al (1997) and Rodriguez et al (1998 (Santiago et al, 2012). These hypermorphic mutations reduce ABA responses and lead to strong insensitivity to ABA in seed germination, root growth, stomatal regulation and gene expression responses (Meyer et al, 1994, Leung et al, 1994, Leung et al, 1997, Rodriguez et al, 1998, Gosti et al, 1999.…”
Section: Protein Phosphatases Type 2c Pp2csmentioning
confidence: 99%
“…However, the recent discovery of the receptors of the plant hormone abscisic acid and its mechanism of action as inhibitors of protein phosphatases (Santiago et al, 2012) has shown that regulation of protein phosphatases can also control phosphorylation signaling cascades. More recently, the plasma membrane H + -ATPase of the plant Arabidopsis thaliana has been reported to be activated by auxin by a mechanism consisting on the inhibition of PP2C-D phosphatases by some SAUR proteins induced by the hormone .…”
Section: Protein Phosphatasesmentioning
confidence: 99%
“…This β-sheet produces a cavity that contains a ligand-binding pocket that closes after ABA binding through conformational changes of two conserved β-loops that serve as gate and latch (Park et al, 2009;Ma et al, 2009;Melcher et al, 2009;Santiago et al, 2012). Comparison of the catalytic core of the different Arabidopsis PP2CAs…”
Section: Aba Signalling Integrationmentioning
confidence: 99%
“…Moreover, it has been demonstrated that ABA binding to the receptors is enhanced when PYR/PYL/RCAR proteins are bound to their negative regulators PP2CAs (Park et al, 2009;Ma et al, 2009;Melcher et al, 2009;Dupeux et al, 2011a;Santiago et al, 2012). After ABA binding, the receptor locks in a closed structure that inhibits the PP2CA active site (Melcher et al, 2009;Santiago et al, 2009b).…”
Section: Aba Signalling Integrationmentioning
confidence: 99%